Evaluation of the efficiency of the pure water service in the district of Qal'at Saleh (Journal of Misan Researches, 2024)
This study was conducted to evaluate the efficiency and quality of pure water produced in the district of Qal'at Saleh and the per capita share of it and its suitability for human consumption in accordance with the Iraqi and international standards and determinants used in this regard and to clarify the problems that the net water production system complains about. The research found that the actual daily production capacity of the stations and the population of the study area do not suffer from a deficit in terms of quantity but are unfit for human consumption in terms of the concentration of chemical elements and bacteria. The actual production of the total stations of the judiciary of pure water has reached (107185 m 3 / day) distributed by (74072 m 3 / day) in the centre of the district of Qal'at Saleh and its villages and countryside and (33113 m 3 / day) in the district of Al-Uzair and its villages. Thus, the per capita share of clear water in the research area has reached (934 litres/day) for the year 2022. It exceeded the Iraqi limit, expressing the per capita need for pure water (360 litres/day).